Work-family guilt: The perspective of secondary school athletic trainers with children - Eason, C. M.; Rynkiewicz, K. M.; Mazerolle Singe, S. (Journal of Athletic Training, 2021)
Context: The literature in athletic training has consistently demonstrated evidence of work-family-life conflict and the potential consequences of that conflict among athletic trainers (ATs) employed in the clinical setting. Parental responsibilities have been suggested to increase the conflict among work, family, and life. The emotions that occur because of this conflict have received little attention and warrant further study. Objective: To investigate perceptions and antecedents of work-family guilt (WFG) among secondary school ATs with children. Design: Phenomenological qualitative study. Setting: Secondary schools. Patients or Other Participants